Conflict of interest in commercial bank security underwritings: Canadian evidence - Hebb, Gregory M; Fraser, Donald R (Journal of Banking & Finance, 2002)
The recent repeal of the Glass–Steagall Act in the US has cleared the way for commercial banks to enter the securities underwriting business. Many of the concerns that resulted in the original passage of the Glass–Steagall Act, however, still exist. One of these is the possible conflict of interest a universal bank faces. This paper provides evidence on this issue from the experience of Canada following its removal of restrictions on chartered bank ownership of investment dealers. Both ex ante bond yield comparisons between commercial and investment bank underwritten issues and equity price reactions to bond issue announcements provide no evidence of a conflict of interest.